Per interposto manoscritto. Didascalie, postille e metapostille nell’avantesto delle 'Rime' di Alfieri (Prassi Ecdotiche della Modernità Letteraria, 2022)
The paper focuses on the pre-text of Vittorio Alfieri’s Rime and analyzes the rubrics, journal-type notes and meta-notes (aimed at contextualize or comment the poems) in order to explore the role given by the author to his draft manuscripts. While Alfieri’s collection of poems has usually been considered as a sort of personal diary in which he made a literary transfiguration of event-based contents, we will  show how Alfieri tends to use his manuscripts to seal his literary self-portrait to his biographical self.
Keywords: Vittorio Alfieri; authorial philology; manuscripts; Rime; autobiography